Educators' Perceptions of a School-Based Antibullying Program in an Elementary School - Sims-Jones, Jacquelyn Andrea (2018)
Bullying is a problem experienced in schools across the country including in the ABC Elementary School in Georgia, where the No Place for Hate antibullying program is in place to address this problem. The purpose of this qualitative case study was to understand educators' perspectives on their experiences implementing the program. Bandura's social learning theory was used as the conceptual foundation for this study. A content analysis research method based on that of Yin and employing NVivo software was used to analyze interviews. The participants were asked to comment on three main areas: (a) bullying, (b) useful components of the No Place for Hate antibullying program, and (c) resources available for them to use in identifying and responding to bullying. The participants were 10 teachers and 3 administrators at ABC Elementary School who were affiliated with the program. Each participant engaged in a semi structured, face-to-face interview lasting approximately 30 to 45 minutes. Teachers and administrators perceived that the No Place for Hate anti-bullying program at ABC Elementary School helped participants to actively acknowledge and respond to the issue of bullying. However, all felt that a more consistent implementation would increase its effectiveness. Educators may use the results of the study through a professional development as a basis for recommendations concerning vital areas of antibullying programs that schools should improve upon or implement. The results of this study added to the body of knowledge for other schools that use or might use the No Place for Hate antibullying program. Moreover, the results of the study could be used to inform federal and state governments concerning the development of sound policies and programs on addressing bullying that may result in safer educational experiences for students